2001
DOI: 10.1074/jbc.m007597200
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Superoxide-producing NAD(P)H Oxidase in Kidney

Abstract: During phagocytosis, gp91phox , the catalytic subunit of the phagocyte NADPH oxidase, becomes activated to produce superoxide, a precursor of microbicidal oxidants. Currently increasing evidence suggests that nonphagocytic cells contain similar superoxide-producing oxidases, which are proposed to play crucial roles in various events such as cell proliferation and oxygen sensing for erythropoiesis. Here we describe the cloning of human cDNA that encodes a novel NAD(P)H oxidase, designated NOX4. The NOX4 protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
423
1
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 467 publications
(440 citation statements)
references
References 39 publications
14
423
1
2
Order By: Relevance
“…The specificity of AA-861, duroquinone, and tBuBQ for Nox4 over Nox2, suggests either a direct effect of quinone derivatives in the molecular dynamics of electron transfer mediated by Nox4, or an indirect role on a quinone sensitive functional partner of Nox4. In this work, we suggest a new aspect of Nox4 oxidase activity regulation that takes place not only at a transcriptional level as usually described [13,27,45] but also at a post-translational level as described above with quinone molecules. Quinones are bioreactive molecules that are sensitive to redox mechanism.…”
Section: Discussionmentioning
confidence: 76%
“…The specificity of AA-861, duroquinone, and tBuBQ for Nox4 over Nox2, suggests either a direct effect of quinone derivatives in the molecular dynamics of electron transfer mediated by Nox4, or an indirect role on a quinone sensitive functional partner of Nox4. In this work, we suggest a new aspect of Nox4 oxidase activity regulation that takes place not only at a transcriptional level as usually described [13,27,45] but also at a post-translational level as described above with quinone molecules. Quinones are bioreactive molecules that are sensitive to redox mechanism.…”
Section: Discussionmentioning
confidence: 76%
“…Furthermore, expression of Nox4 was also detected in renal cell carcinoma (Shiose et al, 2001) and glioblastoma (Cheng et al, 2001), implying the possible role of Nox4-generated ROS in maintenance of transformation phenotypes. We have recently found that Nox1 is functionally required for maintenance of Ras-induced transformation phenotypes (Mitsushita et al, 2004).…”
Section: Discussionmentioning
confidence: 96%
“…Nox4 is expressed in high levels in kidney [99,100], while other Nox1, Nox2 and Nox regulatory subunits are expressed at lower but quantitatively significant levels [101,102], making Nox enzymes attractive candidates for the origin of renal ROS including the relatively high levels of H 2 O 2 seen in urine. In kidney, Nox-dependent ROS is produced in response to agonists that bind to D1-like receptors [103], to Angiotensin II [104,105] and to H + fluxes [106].…”
Section: Nox Enzymes Ros and Renal Disease A Renal Nox Enzymesmentioning
confidence: 99%
“…In kidney, Nox-dependent ROS is produced in response to agonists that bind to D1-like receptors [103], to Angiotensin II [104,105] and to H + fluxes [106]. Although physiological roles are not well understood, Nox enzymes have been suggested to function in normal renal physiology in secretion of erythropoietin [100], in renal regulation of blood pressure [103], regulation of mesangial cell protein synthesis [107] and in innate immunity [23]. In addition to their normal roles in renal physiology, Nox-generated ROS are implicated in the pathogenesis of variety of kidney-related diseases:…”
Section: Nox Enzymes Ros and Renal Disease A Renal Nox Enzymesmentioning
confidence: 99%